2004
DOI: 10.1002/ffj.1353
|View full text |Cite
|
Sign up to set email alerts
|

Composition of seeds and stems essential oils of Pituranthos scoparius (Coss. & Dur.) Schinz

Abstract: The composition of the essential oils of stems and seeds of Pituranthos scoparius was determined by GC-MS. Almost 50 compounds were identified. In the seed oil, the main compounds were α α α α α-pinene (8.2%), β β β β β-pinene (4.6%), p-cymene (7.5%), limonene (11.2%), thymol (5.9%), myristicin (11.1%) and dill apiole (12.2%); in the stem oil, the main compounds were α α α α α-pinene (6.8%), α α α α α-phellandrene (7.1%), limonene (9.8%), methyl eugenol (5.6%) germacrene D (12.7%), myristicin (7.2%), spathulen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 6 publications
1
10
2
Order By: Relevance
“…The chemical profile of the essential oil from the present study is similar to that reported by (Vérité et al, ), but the contents of major components are different, so that those reported in our study are higher. Also, sabinene is reported to be the most abundant compound in our study, whereas no trace of this compound was reported in the study of the previous authors.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The chemical profile of the essential oil from the present study is similar to that reported by (Vérité et al, ), but the contents of major components are different, so that those reported in our study are higher. Also, sabinene is reported to be the most abundant compound in our study, whereas no trace of this compound was reported in the study of the previous authors.…”
Section: Resultssupporting
confidence: 90%
“…Reports of the chemical profile of the essential oils of P. scoparius are very limited. We report mainly the work of (Vérité, Nacer, Kabouche, & Seguin, ) on stems and seeds of P. scoparius (Boutaghane et al, ) on their antibacterial activities and more recently the work of (Lograda, Ramdani, Kiram, Chalard, & Figueredo, 2013) on the variation of the essential oils compositions of P. scoparius collected from different locations in Algeria.…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative and quantitative differences between this study and those of others authors cited in the literature could be due to the existence of different chemotypes of P. scoparius collected from different regions of Algeria [3,6]. These sorts of variations are due to climatic and geographical conditions (difference of period and of geographic area of collection).…”
Section: Discussioncontrasting
confidence: 63%
“…The Touareg people are little communities living in the Algerian desert of Tassili and Hoggar, use this aromatic plant for flavoring various feed such as meat and bread. P. scoparius is widely used in Algerian traditional medicine for the treatment of asthma and rheumatism, postpartum care, spasms, pains, fevers, diabetes, lice (head and pubis), hepatitis, digestive difficulties, urinary infections and scorpions tings [3,4]. Previous studies have shown various chemical compositions of essential oils of P. scoparius.…”
Section: Introductionmentioning
confidence: 99%
“…The species Pituranthos chlorantus in folk medicine is generally used as Fever, diabetes asthma, rheumatism (Hammiche et al, 2006;Vérité et al, 2004).…”
Section: Introductionmentioning
confidence: 99%